Construction of a Recombinant Plasmid from Newcastle Disease Virus Antigen, Haemagglutinin-Neuraminidase and Lactococcal N-Acetylmuramidase and its Expression - Yasid, Nur Adeela (2009)
The anchoring of proteins to the cell surface of Lactococcus using recombinant DNA techniques is an exciting and emerging research area that holds great promise for a wide variety of biotechnological applications. Presently available anchoring systems are based on recombinant bacteria displaying proteins or peptides on the cell surface. This research is focused on using lactococcal cell wall binding (cwb) region for display of viral epitopes and antigenic determinants. Newcastle disease virus (NDV) is the aetiological agent of Newcastle disease which can result in 100% morbidity and mortality in chicken. Immune response of haemagglutinin-neuraminidase (HN) protein antigens of NDV plays an important role in the prevention of viral infection. A lactococcal domain coding region, acmA’ (300 bp) was cloned into the mammalian expression vector, pcDNA3.1/His. The 1.7 kb HN gene was then inserted at the 5’-end of the acmA’ coding region. Plasmid extraction and restriction enzyme digestion analyses showed that cloning was carried out successfully. Sequencing results indicated that the inserts (acmA’, HN and acmA’HN) were 99%, 97% and 98% homologous to the published sequence of Lactococcus lactis and NDV strain AF2240. The condition for transfection was optimised by testing various amounts of transfected DNA (1 μg, 2 μg and 3 μg) and different charge ratio of liposome reagent (μl): DNA (μg) in a 6-well plate. Transient expression of the fusion protein in Chinese hamster ovary (CHO) cells was analysed by SDS-PAGE and Western blotting. The results indicated that the best combination of DNA used for transfection was 2 μg in 1:3 charge ratio of the liposome:DNA. This study showed that a recombinant acmA’, HN and acmA’-HN have been successfully constructed, transfected and expressed in CHO cells. This work could contribute towards the development of a recombinant vaccine delivery system for NDV.